2012
DOI: 10.2466/30.22.23.pms.115.6.969-983
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Strategies for Goalkeeper Responding to Soccer Penalty Kick

Abstract: The main aim of the present study was to examine how a goalkeeper's response-initiation time influences the accuracy of the response to a soccer penalty kick. The participants were 24 university male students in two groups: 12 experienced soccer goalkeepers, and 12 experienced soccer field players. They were required to watch videos made by three different kickers preparing a penalty kick, then 12 ensuing moments, occluded 467 msec. before impact of the kicker's foot with the ball to 267 msec. after impact. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
7
0
2
Order By: Relevance
“…However, in recent years, attempts have been made to better understand and explain their outcomes scientifically [10][11][12][13][14][15][16]. It appears that many variables including kicking technique, visual search strategies, tactical skills and fitness contribute to the performance of penalty takers, alongside basic "chance" [17,18]. However, psychological factors are reportedly the most influential determinant of penalty outcomes [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, attempts have been made to better understand and explain their outcomes scientifically [10][11][12][13][14][15][16]. It appears that many variables including kicking technique, visual search strategies, tactical skills and fitness contribute to the performance of penalty takers, alongside basic "chance" [17,18]. However, psychological factors are reportedly the most influential determinant of penalty outcomes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Alguns estudos observacionais usaram dispositivos e recursos tecnológicos para analisar o chute, enfocando variáveis como velocidade da bola (Markovic, Dizdar & Jaric, 2006;Van den Tilaar & Ulvik, 2014), os movimentos oculares dos jogadores (Giagazoglou, Katis, Kellis & Natsikas, 2011;Peiyong & Inomata, 2012), a potência e a posição do pé durante as repetições do movimento do chute (Shan & Westerhoff, 2005;Inoue, Nunome, Sterzing, Shinkai & Ikegami, 2014), tanto em condições estáticas, realizando os chutes com a bola parada (Wilson, Wood & Vine 2009;Button, Dicks, Haines, Barker & Davids, 2011), como em condições dinâmicas, executando o chute com a bola em movimento (Shinkai, Nunome, Isokawa & Ikegami, 2009). Os dados tem apontado que as atividades musculares de outras partes do corpo (tronco, abdômen, ombros e braços), bem como os movimentos oculares do batedor, influenciam na velocidade e na potência do chute (Markovic, Dizdar & Jaric, 2006;Van den Tilaar & Ulvik, 2014;Giagazoglou et als, 2011).…”
Section: Estudos Realizados Para Verificar a Precisão Dos Chutes Em Aunclassified
“…A player’s skill level has been proposed as a relevant variable influencing an athlete’s use of probabilistic information. Previous research has reported better use of contextual information among expert athletes compared to novices, both in laboratory settings and real game scenarios, with skill helping athletes initiate a faster response (Farrow & Reid, 2012; Peiyong & Inomata, 2012) or a response with greater accuracy (Abernethy et al., 2001; Farrow & Abernethy, 2003; Loffing & Hagemann, 2014; Roca et al., 2013; Ward & Williams, 2003). For example, Abernethy et al.…”
Section: Introductionmentioning
confidence: 99%
“…In tennis, Farrow and Abernethy (2003) showed that expert tennis players were better than novices at predicting the direction of an opponent's serve. In football, expert players used contextual information based, on structural relations between counterparts, teammates and ball (Williams et al., 2006) to: (a) accurately anticipate the final destination of passes in 11 vs. 11 situations (Ward & Williams, 2003); (b) modify their perceptual and anticipatory behaviors according to the distance between the ball and the goal (Roca et al., 2013); and (c) anticipate a goalkeeper's responses (Peiyong & Inomata, 2012). In karate, Milazzo et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation